Regional convergence in asean-5 countries : a time series analysis - Ngu, Nyok Ping (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The objective of this study was to investigate the regional convegence in ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore and Thailand) in the yea of 1970 to 2009. Empirical results from the unit roots test lend to support to the evidence of the stochastic convergence among the ASEAN-5 countries since 1970.